Mineralocorticoid Receptor Signaling Contributes to Normal Muscle Repair After Acute Injury - Hauck, J. Spencer; Howard, Zachary M.; Lowe, Jeovanna; Rastogi, Neha; Pico, Madison G.; Swager, Sarah A.; Petrosino, Jennifer M.; Gomez-Sanchez, Celso E.; Gomez-Sanchez, Elise P.; Accornero, Federica; Rafael-Fortney, Jill A. (Frontiers in Physiology, 2019)
Acute skeletal muscle injury is followed by a temporal response of immune cells, fibroblasts, and muscle progenitor cells within the muscle microenvironment to restore function. These same cell types are repeatedly activated in muscular dystrophy from chronic muscle injury, but eventually, the regenerative portion of the cycle is disrupted and fibrosis replaces degenerated muscle fibers. Mineralocorticoid receptor (MR) antagonist drugs have been demonstrated to increase skeletal muscle function, decrease fibrosis, and directly improve membrane integrity in muscular dystrophy mice, and therefore are being tested clinically. Conditional knockout of MR from muscle fibers in muscular dystrophy mice also improves skeletal muscle function and decreases fibrosis. The mechanism of efficacy likely results from blocking MR signaling by its endogenous agonist aldosterone, being produced at high local levels in regions of muscle damage by infiltrating myeloid cells. Since chronic and acute injuries share the same cellular processes to regenerate muscle, and MR antagonists are clinically used for a wide variety of conditions, it is crucial to define the role of MR signaling in normal muscle repair after injury. In this study, we performed acute injuries using barium chloride injections into tibialis anterior muscles both in myofiber MR conditional knockout mice on a wild-type background (MRcko) and in MR antagonist treated wild-type mice. Steps of the muscle regeneration response were analyzed at one, four, seven, or fourteen days after injury. Presence of the aldosterone synthase enzyme was also assessed during the injury repair process. We show for the first time aldosterone synthase localization in infiltrating immune cells of normal skeletal muscle after acute injury. MRcko mice had an increased muscle area infiltrated by aldosterone synthase positive myeloid cells compared to control injured animals. Both MRcko and MR antagonist treatment stabilized damaged myofibers and increased collagen infiltration or compaction at four days post-injury. MR antagonist treatment also led to reduced myofiber size at seven and fourteen days post-injury. These data support that MR signaling contributes to the normal muscle repair process following acute injury. MR antagonist treatment delays muscle fiber growth, so temporary discontinuation of these drugs after a severe muscle injury could be considered.